STRUCTURE OF THE PIGMENT OF MACPALXOCHITL - SODI PALLARES, ERNESTO; MARTINEZ GARZA, HECTOR (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1910)
Over 500 serum specimens chosen from individuals having had a history of typhus fever in various parts of Mexico were tested against specific classic and murine typhus antigens according to the technique of Plotz, Wertman, and Bennett 184 out of 237 posi
ARCH BIOCHEM BIOPHYS
Keywords: STRUCTURE, PIGMENT, MACPALXOCHITL; CIENCIAS DE LA VIDA; BIOLOGIA MOLECULAR; BIOLOGIA MOLECULAR DE MICROORGANISMOS